Mechanosynthesis of metastable cubic δ-Ta1−xN - Garcia-Mendoza, T.; Martínez García, Alfredo; Becerril-Juarez, I. G.; Lopez-Vazquez, E.; Avalos-Borja, M.; Valera Zaragoza, Mario; Juárez Arellano, Erick Adrián (Ceramics International, 2020)
The formation of the cubic δ-Ta₁−xN phase by high-energy ball-milling from tantalum and boron nitride (h-BN) is explored. Two different molar ratios Ta:BN, 1:1 and 2:1, were used. X-ray diffraction, scanning electron microscopy, surface area analysis by the Brunauer–Emmett–Teller method, and thermogravimetric analysis were used to characterize the products obtained. In both molar ratios and after a few minutes of milling, the mechanosynthesis of δ-Ta₁−xN was observed. Increasing the entropy of the system by introducing vacancies and point defects through the high-energy ball-milling process seems to stabilize the cubic δ-Ta₁−xN phase, as previous theoretical studies had reported. The phase obtained depends on the molar ratio used: at a 1:1 molar ratio, a non-stoichiometric δ-Ta₁−xN phase is obtained, while at a 2:1 molar ratio, a stoichiometric δ-TaN phase and secondary phases are formed. Amorphous boron remains dispersed in the material until the mechanical energy is high enough to trigger the formation of tantalum borides.
Keywords: Nitruro de tantalio; Fase metaestable; Molienda de bolas de alta energía